2020
DOI: 10.1155/2020/7986249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress on Autonomic and Cardiovascular Systems in Military Population: A Systematic Review

Abstract: Stress is regulated by the autonomous nervous system, increasing the sympathetic modulation when a threat is perceived. A multifactorial response usually leads to significant behavioural modifications and alterations on homeostasis and physical and psychological status. Moreover, stress is an emotional response that can lead to psychosocial and psychophysiological adversity. Regarding military population, military operations and combat exposure are important stressors that influence acute and chronic stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 35 publications
(81 reference statements)
2
35
0
3
Order By: Relevance
“…The effects of stress through autonomic system analysis have been studied in several groups of subjects. A recent systematic review from Bustamante et al [ 54 ] focused on the effects of stress in the military population and the consequences for their autonomic balance, enhancing the necessity for finding coping strategies [ 55 , 56 , 57 ]. Other authors have also explored autonomic balance in several sports [ 47 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], enhancing the importance of PNS activation in performance.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of stress through autonomic system analysis have been studied in several groups of subjects. A recent systematic review from Bustamante et al [ 54 ] focused on the effects of stress in the military population and the consequences for their autonomic balance, enhancing the necessity for finding coping strategies [ 55 , 56 , 57 ]. Other authors have also explored autonomic balance in several sports [ 47 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], enhancing the importance of PNS activation in performance.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic activation could induce increased anaerobic metabolism or increased anxiety and stress perceptions among other psychophysiological effects [ 17 ]. Autonomic modulation analysis was used in a military population as a stress marker, showing how different military manoeuvres, independently of land or flight units, produced an increased sympathetic modulation [ 18 ]. Moreover, the fatigue induced by flights can also be detected by spirometry, handgrip strength, and stress and exertion rates as previous authors showed in this special population [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the HR and SatO2 increased after the crane rescue maneuver, showing the organic adaptive response to the cardiorespiratory demands of the maneuver. This response was contrary to the low-altitude flight and other military combat situations where SatO2 decreased in the interventions [3,5,[7][8][9][10][11]13,27]. The higher demands of the crane rescue maneuver could be responsible for the decreases in the horizontal jump, FEV1, PEF, and ST • , which are signals of fatigue [5].…”
Section: Discussionmentioning
confidence: 85%
“…This response is in line with results obtained in armies and militaries in different combat maneuvers (asymmetrical, symmetrical, urban combat, etc. ), highlighting the importance of HRV control and the application of correct training to improve the autonomic response in these high-stress situations [27].…”
Section: Discussionmentioning
confidence: 99%